Fikih Learning Through Differentiated Models: Pembelajaran Fikih Melalui Model Diferensiasi - Astuti, Mayang Sari; Azis, Abdul; Anshari, Muhammad Redha (Halaqa: Islamic Education Journal, 2025)
General Background: Differentiated learning has emerged as a key pedagogical strategy to address diverse student needs in contemporary education. Specific Background: In religious education, particularly Fikih subjects, individualized approaches remain underexplored despite their potential to enhance engagement and comprehension. Knowledge Gap: Limited studies have examined the implementation of differentiated learning in Islamic education settings, especially in Indonesian madrasahs. Aims: This study investigates the implementation of differentiated learning in Fikih subjects at MAN Kota Palangka Raya and its effects on student engagement and understanding. Results: Using a qualitative method involving observation, interviews, and documentation, the study reveals that differentiated instruction—tailored to students’ readiness, interests, and learning styles—significantly boosts motivation, confidence, and comprehension. Teachers employ varied strategies, including discussions, projects, experiments, and digital integration. Formative assessments show improved conceptual understanding and real-life application. Novelty: This study provides empirical evidence on the practical application of differentiated learning in Islamic education, an area with limited research. Implications: Findings highlight the need for institutional support, such as teacher training and adequate facilities, to overcome challenges and optimize learning. The research underscores the potential of differentiated learning to transform Fikih education into a more inclusive, relevant, and effective experience. Highlights: Enhances student motivation and comprehension. Adapts teaching to students’ needs and learning styles. Requires institutional support for effective implementation. Keywords: Differentiated Learning, Fikih Education, Student Engagement, Islamic Education, Instructional Strategy